Click reactive microgels as a strategy towards chemically injectable hydrogels. Issue 44 (19th October 2016) - Absil, Rémi; Çakir, Seda; Gabriele, Sylvain; Dubois, Philippe; Barner-Kowollik, Christopher; Du Prez, Filip; Mespouille, Laetitia
Abstract : Doubly crosslinked microgels (DX microgels) are hydrogels constructed by covalently interlinked microgel particles, offering two levels of hierarchy within the network, the first one being the microgel and the second being the interlinked microgel network. Abstract : Doubly crosslinked microgels (DX microgels) are hydrogels constructed by covalently interlinked microgel particles, offering two levels of hierarchy within the network, the first one being the microgel and the second being the interlinked microgel network. Herein we describe an efficient approach for DX microgel synthesis via the ultrafast triazolinedione (TAD)-based click reaction. Cyclopentadienyl functional microgels were prepared by a conventional water in oil (W/O) suspension, free-radical copolymerization of poly(ethylene glycol)methyl ether methacrylate ( M n = 500 g mol −1 ) with glycidyl methacrylate and ethylene glycol dimethacrylate as crosslinkers. Microgel post-modification was subsequently achieved by reacting glycidyl functions with sodium cyclopentadienide (NaCp), resulting in Cp-functionalized microgels. Finally, the microgels were mixed with a bis-TAD functional crosslinker, resulting in crosslinking with adequate kinetics (minutes to seconds) to form a doubly crosslinked microgel network. Size distributions of swollen microgels before creation of the second network were followed by optical microscopy and particle size measurements. The efficient functionalization of the microgels with Cp units was demonstrated by a fluorescence labelling study. Dynamic rheology data showed the increase of mechanical properties from the microgels to the doubly crosslinked microgel network formed after addition of the TAD crosslinker. The current study thus highlights the efficiency of catalyst free modular ligation chemistry to synthesize DX microgels with a very fast gelation process from 5 minutes to 15 seconds depending on the crosslinker to Cp ratio, from 0.7 to 1 respectively.